Scar Formation, Healing Stages, and Advanced Treatment Strategies – Review - Do, Monika Kienanh; Mikusek-Pham Van, Marcin; Zaliwska , Dominika; Kraszkiewicz, Adrianna; Paduszyńska, Natalia; Gonciarz, Marta Justyna; Adamiec, Dominika Karolina; Dąbrowska, Anna; Kamińska, Monika Anna; Czach, Magdalena (Quality in Sport, 2024)
Introduction and Aim of the Study: Scarring is a major concern in clinical dermatology, affecting individuals’ quality of life due to both physical and psychological impacts. This review aims to explore the pathophysiology of various scar types—hypertrophic, keloid, and atrophic—and evaluate the effectiveness of current and emerging treatments to inform better clinical practices and therapeutic strategies. Description of the State of Knowledge: Scar formation involves complex biological processes: inflammation, proliferation, and remodeling. The nature of the scar varies with the underlying cause and biological response, influenced by genetic factors, skin tension, and environmental elements such as UV exposure. Recent advances in treatments range from surgical techniques to laser therapy and biological agents like cytokines. Conclusion: The studies reviewed underscore the complexity of scar management, influenced by diverse genetic, biological, and environmental factors. No single treatment is universally effective, but a combination of preventative and therapeutic strategies shows the best promise.